A new species of Tetrastichus Haliday (Hymenoptera: Eulophidae) parasitizing the rice case worm, Parapoynx stagnalis (Zeller) (Lepidoptera: Crambidae) from India. (3rd April 2017) - Santhosh, Shreevihar; Karthikeyan, Kolandhaivelu
Abstract: Tetrastichus paraponyxi Santhoshsp. nov. (Hymenoptera: Eulophidae, Tetrastichinae), a new pupal parasitoid of the rice case worm, Parapoynx stagnalis (Zeller) (Lepidoptera: Crambidae), a pest of paddy, Oryza sativa L. (Poaceae) from India is described.